Relating Sublinear Space Computability Among Graph Connectivity and Related Problems - Imai, Tatsuya; Watanabe, Osamu (SOFSEM 2016: Theory and Practice of Computer Science, 2016)
We investigate sublinear-space computability relation among the directed graph vertex connectivity problem and its related problems, where by “sublinear-space computability” we mean in this paper $$O(n^{1-ε })$$ -space and polynomial-time computability w.r.t. the number n of vertices. We demonstrate algorithmic techniques to relate the sublinear-space computability of directed graph connectivity and undirected graph length bounded connectivity.